Delaying Onset of Dementia: Are Two Languages Enough? - Morris Freedman; Suvarna Alladi; Howard Chertkow; Ellen Bialystok; Fergus I. M. Craik; Natalie A. Phillips; Vasanta Duggirala; Surampudi Bapi Raju; Thomas H. Bak (Behavioural Neurology)
There is an emerging literature suggesting that speaking two or more languages may significantly delay the onset of dementia. Although the mechanisms are unknown, it has been suggested that these may involve cognitive reserve, a concept that has been associated with factors such as higher levels of education, occupational status, social networks, and physical exercise. In the case of bilingualism, cognitive reserve may involve reorganization and strengthening of neural networks that enhance executive control. We review evidence for protective effects of bilingualism from a multicultural perspective involving studies in Toronto and Montreal, Canada, and Hyderabad, India. Reports from Toronto and Hyderabad showed a significant effect of speaking two or more languages in delaying onset of Alzheimer’s disease by up to 5 years, whereas the Montreal study showed a significant protective effect of speaking at least four languages and a protective effect of speaking at least two languages in immigrants. Although there were differences in results across studies, a common theme was the significant effect of language use history as one of the factors in determining the onset of Alzheimer’s disease. Moreover, the Hyderabad study extended the findings to frontotemporal dementia and vascular dementia.